Testing environmental Kuznets curve hypothesis: the role of enterprise’s sustainability and other factors on GHG in European countries - Lapinskienė, Giedrė; Peleckis, Kęstutis; Nedelko, Zlatko (Journal of Business Economics and Management, 2017)
The paper analyses the environmental Kuznets curve relationship between greenhouse gases and chosen indicators of economic development based on the panel data of 20 countries of the EU in the period 2006–2013. Besides the typical variables, such as the share of a particular polluting industry, environmental taxes, energy taxes, research and development, the dummy variable of the crises and enterprise’s sustainability score were also included in the model. The fixed effect panel model was used as a framework for the analysis. The original contribution of this paper is that the factor referring to the enterprises’ sustainability was empirically tested in the expanded model. Higher energy taxes, research and development and the number of sustainable enterprises decrease the level of greenhouse gases. The size of agriculture, production and construction has a positive sign, which means that a higher value of the indicator is associated with a higher level of greenhouse gases. This implies that the analysed set of factors can be applied to adjust the trend in the region and might be useful for the climate change policy adjustment.